THE IMPACT OF FINANCIAL LITERACY AND PERSONALITY TO FINANCIAL MANAGEMENT BEHAVIOR ON SMES, GENDER AS MODERATING: A REVIEW - Gunartin, Gunartin; Susanto, Susanto; Kurniawan, Wiwit (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Small and medium-sized enterprises (SMEs) are of significant importance in the global economy; however, they encounter higher rates of failure in comparison to larger corporations, primarily attributable to issues related to financial mismanagement. The objective of this study is to examine the influence of financial literacy and personality traits on the financial management practices of SMEs, with a particular focus on how gender may moderate these relationships. There exists a positive correlation between financial literacy and financial management behavior, with this relationship being further influenced by individual levels of self-control and risk aversion. The primary objective of this research is to examine the correlation between financial literacy, personality traits, and financial management practices within SMEs. Additionally, this study will specifically explore the potential moderating effects of gender on these relationships. This study aims to investigate a connection between financial expertise, personality attributes, and the financial management behavior of SMEs by conducting a thorough examination of the available literature. It is worth noting that personality factors seem to have a more significant impact on male SMEs owners in comparison to their female counterparts. This observation implies that personality traits may exert a stronger influence on the financial management practices of male SME owners. The implications of these findings hold substantial importance for SMEs owners and policymakers. The findings emphasize the significance of SME owners augmenting their financial literacy and enhancing their financial management abilities. Enhancing financial education programs that are specifically tailored for SMEs has the potential to empower business owners by equipping them with the knowledge and skills necessary to make well-informed financial decisions and proficiently manage their resources. It is imperative for policymakers to give precedence to the advancement and execution of all-encompassing financial literacy initiatives that take into account the moderating influences of personality traits and gender. Through the implementation of these measures, SMEs proprietors can optimize their financial management methodologies, minimize potential hazards, and make valuable contributions to the prosperity and longevity of SMEs. This will yield advantages for both individual enterprises and the wider economy.